Haemophilus aphrophilus and Eikenella corrodens Coinfection of Brain: An Unusual Case from China - Yuan L; Lai LM; Zhu X; Rui Z; Liu Y; Chen Q (Infection and Drug Resistance, 2024)
Lei Yuan,* Lan Min Lai,* Xinyu Zhu, Zhao Rui, Yang Liu, Qiang Chen Department of Clinical laboratory, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang Chen, Email 674389899@qq.comBackground: The HACEK group comprises Haemophilus spp., Aggregatibacter actinomycetemcomitans, Cardiobacterium hominis, Eikenella corrodens, and Kingella kingae, are Gram-negative bacteria that are slow-growing and fastidious. These organisms are common causes of culture-negative endocarditis. However, brain abscesses caused by Haemophilus aphrophilus and E. corrodens have been rarely reported. The case we describe, which was promptly identified and successfully treated, will be meaningful for the diagnosis and treatment of such infectious diseases.Case Presentation: Herein, we report a case of brain abscess in a young man who was infected with Haemophilus aphrophilus and E. corrodens. The patient was admitted to the hospital with sudden onset of vomiting, coma, and fever. Magnetic resonance imaging (MRI) of the brain and cerebrospinal fluid cell counts suggested cerebral abscess, he underwent drainage of the abscess and empirical antimicrobial therapy of meropenem (2 g every 8 hours) and linezolid (0.6 g every 12 hours) for more than 10 days without significant improvement. Metagenomic next-generation sequencing (mNGS) of drainage fluid and matrix-assisted laser desorption ionization–time-of-flight mass spectrometry (MALDI-TOF MS) detection for isolated bacteria from samples suggested the presence of H. aphrophilus and E. corrodens. After 7 weeks of ceftriaxone (2 g every 12 hours) and meropenem (2 g every 8 hours) intravenously, the patient was discharged with a normal temperature and brain MRI showed improvement of the lesion.Conclusion: Similar cases reported in previous studies were always associated with bacterial blood dissemination after dental surgery or myocarditis; however, the patient in our case had no any associated risk factors. As far as we know, this is the only case of central nervous system infection caused by H. aphrophilus and E. corrodens that has utilized combined mNGS and MALDI-TOF MS in the diagnosis.Keywords: Haemophilus aphrophilus, Eikenella corrodens, HACEK, brain abscess